2019
DOI: 10.1002/cctc.201802048
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate as an Efficient Amine Donor for the Synthesis of Chiral β‐ and γ‐Amino Acids Using Transaminase

Abstract: A recyclable glutamate amine donor system employing transaminase (TA), glutamate dehydrogenase (GluDH) and mutant formate dehydrogenase (FDHm) was developed, wherein amine donor Glu was regenerated using GluDH and thereby circumvented the inhibition of TA by α‐ketoglutarate. Various enantiopure β‐, γ‐amino acids, and amines were successfully synthesized with high conversions and excellent enantiomeric excess using this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…One of the well-known examples of medications with β-amino acids as essential ingredients is sitagliptin, an inhibitor of dipeptidyl peptidase 4 that is used as an oral diabetic medication ( Savile et al, 2010 ; Kim et al, 2019 ; Khobragade et al, 2021 ; Kaur and Jana, 2023 ). In our previous research, the sitagliptin intermediate was produced employing TA from Ilumatobacter coccineus (TAIC, TA 3 ) from the ethyl 3-oxo-4-(2,4,5-trifluorophenyl) butanoate as a substrate ( Khobragade et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the well-known examples of medications with β-amino acids as essential ingredients is sitagliptin, an inhibitor of dipeptidyl peptidase 4 that is used as an oral diabetic medication ( Savile et al, 2010 ; Kim et al, 2019 ; Khobragade et al, 2021 ; Kaur and Jana, 2023 ). In our previous research, the sitagliptin intermediate was produced employing TA from Ilumatobacter coccineus (TAIC, TA 3 ) from the ethyl 3-oxo-4-(2,4,5-trifluorophenyl) butanoate as a substrate ( Khobragade et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…369 In the presence of an (S)-transaminase from E. aerosaccus the b-oxoacid was subsequently converted to L-290 at the expense of 3-aminobutyric acid (240) as the amine donor (82% conversion to product, 499% ee). (S)-transaminases from Sphaerobacter thermophilus, 370,371 Polaromonas sp. 372 and a b-amino acid dehydrogenase from Candidatus cloacamonas acidaminovorans have also been proven capable of catalysing said transformation.…”
Section: Scheme 55 Chemoenzymatic Route Towards Oseltamivir As Develomentioning
confidence: 99%
“…It has been reported that use of purified enzyme system for biocatalytic purposes costs approximately ten times more than that by whole-cell biotransformations [43,44]. Although the use of purified enzymes is limited for their application on large scales, another form of biocatalysts, i.e., cell-free extracts, is feasible if expression levels of the target protein are sufficient [45,46]. However, cell free extracts are unstable.…”
Section: Kinetic Resolution Of Racemic Amines Using E Coli Whole Celmentioning
confidence: 99%